2016
DOI: 10.1007/s00109-016-1410-7
|View full text |Cite
|
Sign up to set email alerts
|

The R130S mutation significantly affects the function of prestin, the outer hair cell motor protein

Abstract: A missense mutation, R130S, was recently found in the prestin gene, SLC26A5, of patients with moderate to severe hearing loss (DFNB61). In order to define the pathology of hearing loss associated with this missense mutation, a recombinant prestin construct harboring the R130S mutation (R130S-prestin) was generated, and its functional consequences examined in a heterologous expression system. We found that R130S-prestin targets the plasma membrane but less efficiently compared to wild-type. The voltage operatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 49 publications
3
15
0
Order By: Relevance
“…We also found punctated mTq2 fluorescence inside the cells regardless of doxycycline dosage (Figure S2). Similar intracellular puncta were also observed in HEK293T cells heterologously expressing ECFP‐tagged prestin (SLC26A5; Takahashi, Cheatham, Zheng, & Homma, ). A recent study also found that SLC26A9 is intracellularly retained when heterologously expressed (Walter, Sawicka, & Dutzler, ).…”
Section: Resultssupporting
confidence: 54%
“…We also found punctated mTq2 fluorescence inside the cells regardless of doxycycline dosage (Figure S2). Similar intracellular puncta were also observed in HEK293T cells heterologously expressing ECFP‐tagged prestin (SLC26A5; Takahashi, Cheatham, Zheng, & Homma, ). A recent study also found that SLC26A9 is intracellularly retained when heterologously expressed (Walter, Sawicka, & Dutzler, ).…”
Section: Resultssupporting
confidence: 54%
“…Unlike the well-studied voltage-sensing domain in the Kv channels (Swartz, 2008), prestin lacks an extensively charged region in the membrane-embedded region (Figures S5E and S5F), and a great deal of effort has been focused on uncovering the prestin voltage-sensing region (Bai et al, 2006(Bai et al, , 2009Gorbunov et al, 2014;Homma et al, 2013;Oliver et al, 2001;Schaechinger et al, 2011;Takahashi et al, 2016;Tan et al, 2012). Mapping the host of residues that affect prestin NLC onto the structure shows that they are spread throughout the sequence and the 3D structure (Figures 1B and S5E).…”
Section: Resultsmentioning
confidence: 99%
“…In all other respects, the subjects were found to be normal. In a transgenic mouse model for the latter mutation membrane, targeting is impaired, kinetics are slowed ( producing a reduced NLC at the measurement frequencies), and transport for thiocyanate is enhanced (Takahashi et al 2016). Apart from one other candidate mutation reported ( p.R150Q) (Toth et al 2007), the p.W70X and the p.R130S are the only deafness-causing mutations identified so far.…”
Section: Genetics: Human Hearingmentioning
confidence: 98%